1999
DOI: 10.1093/fampra/16.2.164
|View full text |Cite
|
Sign up to set email alerts
|

The role of general practice in promoting teenage health: a review of the literature

Abstract: Walker ZAK and Townsend J. The role of general practice in promoting teenage health: a review of the literature. Family Practice 1999; 16: 164-172. Background and methods. Teenagers are acknowledged to be at high risk of health-damaging behaviours including smoking, teenage pregnancy, and drug and alcohol use. Additionally, the recognition of high levels of psychological distress is cause for serious concern about teenage health. This paper reviews health promotion interventions for teenagers in general practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 50 publications
0
36
0
3
Order By: Relevance
“…[12][13][14]17 Findings from studies done in the United Kingdom similarly have found that issues related to confidentiality and embarrassment influence the health care-seeking behavior of youth more than cost. 18,19 Many young people in the U.K. report that they do not turn to others for help with sexual health problems. 20 In sub-Saharan Africa, sexual and reproductive health services generally target older married women, although there are a few service centers that also serve single young men and women.…”
mentioning
confidence: 99%
“…[12][13][14]17 Findings from studies done in the United Kingdom similarly have found that issues related to confidentiality and embarrassment influence the health care-seeking behavior of youth more than cost. 18,19 Many young people in the U.K. report that they do not turn to others for help with sexual health problems. 20 In sub-Saharan Africa, sexual and reproductive health services generally target older married women, although there are a few service centers that also serve single young men and women.…”
mentioning
confidence: 99%
“…This has worrying implications for health service aims to improve teenage health in general, and sexual health in particular. [1][2][3]14 An aim of primary care should be to encourage attendance for all teenagers when they have health concerns. This study suggests that there is a continuing need to change teenagers' perceptions and skills as well as improving services.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Many reports of teenage opinions on services indicate that present services could be improved. [4][5][6][7][8][9][10] It is suggested that 'satisfied' teenagers will use primary care services appropriately.…”
Section: Introductionmentioning
confidence: 99%
“…The Centers for Disease Control define adolescence from age 10 to 24 years, the Maternal Child Health Bureau defines adolescence from age 11 to 21 years, and according to WHO definition adolescents are persons between 10 -19 years. Adolescence is further divided into early, middle, and late (1,2). Adolescence is a period of rapid transition as adolescents go through many physical, psychological, sexual and behavioral changes.…”
Section: Introductionmentioning
confidence: 99%
“…Most mortality in adulthood has its roots in the adolescent period. WHO estimates that 70% of premature deaths among adults are due to behaviors initiated during adolescence (2,4).…”
Section: Introductionmentioning
confidence: 99%